The Influence of Financial Technology and Locus of Control on Financial Behavior of Students in Karang Taruna Cendrawasih Village Madurejo Yogyakarta - Fadhilah, Lia Nur (Management Research Studies Journal, 2025)
This study aims to determine the effect of financial behavior through financial technology and locus of control on students of Karang Taruna Cendrawasi in Madurejo village. In this study, the population consisted only of students of Karang Taruna Cendrawasi in Madurejo village and 100 students registered as members of Karang Taruna were used as samples taken using the random sampling method. The data used were primary data obtained from questionnaires distributed online. Classical hypothesis testing and multiple regression analysis using the SPSS V25.0 program were used for data analysis. Based on the results obtained, it can be concluded that: (1) the financial technology variable has a positive insignificant effect on the financial behavior variable, (2) the locus of control variable has a negative insignificant effect on the financial behavior variable of Karang Taruna Cendrawasi students in Madurejo village. (3) And simultaneously the financial technology and locus of control variables have a positive significant effect on the financial behavior variable of Karang Taruna Cendrawasi students in Madurejo village.